Israel : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Israel. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights the sound economic growth enjoyed by Israel, estimated at 4 percent in 2016 and supported by strong domestic demand and an export rebound. Unemployment declined to 4.4 percent in the fourth quarter of 2016, and wage increases have picked up. Nonetheless, inflation remained below the 1-3 percent target range of the Bank of Israel, reflecting external factors and government measures to reduce the cost of living. Israel's near-term economic outlook is positive. Growth is expected to settle at about 3 percent, and inflation is likely to rise gradually, although with significant uncertainty around the timing of such a rise.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet